A306 TURBULENT HEAT TRANSFER THROUGH A HEAT EXCHANGER WITH POROUS TWISTED TAPE INSERTS(Heat Transfer-2) - Smith EIAMSA-ARD; K. WONGCHAREE; S. RATTANAWONG; Petpices EIAMSA-ARD; M. PIMSARN; Chinaruk THIANPONG (My University, 2009)
In this present work, the influences of the porous twisted tape (PT) on the heat transfer and the pressure loss are studied experimentally. The comparative experiments are conducted in the tube fitted with the PT or typical twisted tape (TT) at different twist ratios, y/w = 4.0 and 5.0, in the Reynolds number ranging from 4800 to 16,000 under uniform heat flux conditions. In the experiments, the PT inserts generate swirls that modify the near wall velocity profile resulted in improvement of the heat transfer rate. The experimental results reveal that the heat transfer rates increase with decreasing twist ratio (y/w) for all twisted tapes used in the experiments. The heat transfer rates increase up to 71% with the help of the PT. The increases in average Nusselt numbers of using PT and TT are found to be 48% and 22%, respectively, over those of the corresponding plain tube. However, PT causes a considerable increase in friction factor. The mean increases of friction factors for PT and TT are respectively, about 3.14 and 2.45 times in comparison with that for the plain tube. Mean friction factor and Nusselt number for PT, are respectively 28% and 21% higher than those for TT. In addition, the empirical correlations of the Nusselt number and friction factor are also reported.
Keywords: Heat transfer enhancement; Friction Factor; Heat Transfer Mechanisms